The Teacher and the Thousand Ways of Doing in the School Daily Life - Flávia Medeiros Sarti (Universidade Estadual Paulista Júlio de Mesquita Filho, 2008)
This article discusses the ways for which the teachers link themselves with speeches that propose innovations for the teaching. Beginning from the considerations of Michel de Certeau concerning the practices of cultural consumption, the "reactionary" character, generally attributed to the educational pedagogic practices, is questioned in opposition to the "revolutionary" tenor that is usually associated to the academic-education speeches. The theme is discussed starting from data gathered in the extent of an ethnographic investigation that focused the reading practices accomplished by teachers inside a program of continuous formation. The results of that study emphasize the existence of specificities in the teaching culture that can be noticed in the ways the teachers conceive the teaching and (re)invent it in the school daily life. The consideration of such aspects makes possible to identify certain limits for the performance of the university in the innovation of the pedagogic practices and in the movement, now in course, of the teaching professionalization. The university is challenged, therefore, to create new forms of relating with the teachers and of acting in his/her professional development.